The effect of oxygen on the composition and microbiology of red wine - Du Toit, Wessel Johannes (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD(Agric) (Viticulture and Oenology))--University of Stellenbosch, 2006.